Exterior material for all-solid-state secondary battery and all-solid-state secondary battery

JP7630707B2Active Publication Date: 2025-02-17KUREHA CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024500952
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-02-16
Filing Date
2022-11-04
Publication Date
2025-02-17
Estimated Expiration
2042-11-04

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、熱融着樹脂を用いた全固体二次電池用外装材であって、熱融着樹脂同士の熱融着部が高温においても高い接着強度を有し、かつ熱融着樹脂のガスバリア性が高い(水蒸気透過性および酸素透過性がいずれも低い)外装材、および当該外装材を有する全固体二次電池が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630707000001
    Figure 0007630707000001
  • Figure 0007630707000002
    Figure 0007630707000002
  • Figure 0007630707000003
    Figure 0007630707000003
Patent Text Reader

Abstract

The present invention provides an outer package material for all-solid-state secondary batteries, the outer package material using a resin which has a melting point that is not as high as those of PET and PPS, while having a high bonding strength after thermal fusion bonding at around 130°C. The above are achieved by an outer package material for all-solid-state secondary batteries, wherein a base material layer, a barrier layer which is formed of a metal or a compound containing a metal, and a thermal fusion bonding layer which has a thickness of 10 µm to 500 µm and contains a polyvinylidene fluoride are sequentially stacked in this order.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an exterior material for an all-solid-state secondary battery and an all-solid-state secondary battery. [Background technology]

[0002] In recent years, interest in environmental issues has increased, and xEVs, which are expected to reduce the environmental impact, are becoming more and more widespread. Non-aqueous electrolyte lithium secondary batteries are widely used as the power source for these vehicles, as they generate a lot of energy. However, the secondary batteries installed in xEVs are large, which means that they generate a lot of heat, and there is a demand for the development of secondary batteries that can operate safely at high temperatures.

[0003] All-solid-state secondary batteries have been attracting attention as an innovative type of secondary battery that can operate safely even at high temperatures. All-solid-state secondary batteries are highly safe batteries that replace the flammable organic electrolyte that constitutes lithium secondary batteries with a non-flammable inorganic solid electrolyte. All-solid-state secondary batteries have a structure in which a battery element that includes a positive electrode, a negative electrode, and a solid electrolyte disposed between them is housed inside a package formed by an exterior material.

[0004] As the exterior material for an all-solid-state secondary battery, a laminate including a base layer, a barrier layer for preventing the intrusion of moisture, and a heat-sealable resin layer is used (for example, Patent Document 1). The battery element is covered by being sandwiched between two sheets of the above-mentioned exterior material from above and below, and the upper and lower exterior materials (heat-sealable resin layers) are heat-sealed at flange portions protruding from the periphery of the battery element, thereby forming an all-solid-state secondary battery in which the battery element is housed inside a package made of the exterior materials.

[0005] Incidentally, all-solid-state secondary batteries have an advantage not found in conventional secondary batteries in that they can be used at temperatures higher than the boiling point of the electrolyte solvent (approximately 80°C) because they do not use an electrolyte. Since the ionic conductivity of a solid electrolyte increases with increasing temperature, using an all-solid-state secondary battery at high temperatures can improve input / output characteristics, etc.

[0006] In order to accommodate use at such high temperatures, high heat resistance is also required for materials for housing the battery elements, such as exterior materials.

[0007] For example, Patent Document 2 describes that the heat resistance of a resin film for terminals, which houses terminals that extract current from electrodes, can be improved by using a thermoplastic resin with a high melting point, such as nylon, polyethylene terephthalate (PET), polyester copolymer, or polyphenylene sulfide (PPS), or a thermosetting resin.

[0008] It is also known that water vapor and the like penetrates into the inside of a battery through heat-sealed portions between heat-sealed resins. If water vapor penetrates into the inside of a battery, the penetrated water vapor may cause deterioration of the performance of the battery element, or if a sulfide is used in the solid electrolyte, the penetrated water vapor may react with the sulfide to generate hydrogen sulfide, so it is necessary to suppress the penetration of water vapor into the inside of the battery. Therefore, the heat-sealed resin used in the exterior material is required to have high gas barrier properties. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] International Publication No. 2020 / 184692 [Patent Document 2] International Publication No. 2020 / 004412 [Patent Document 3] International Publication No. 2020 / 153458 Summary of the Invention [Problem to be solved by the invention]

[0010] In order to use an all-solid-state secondary battery at high temperatures, it is required to improve the heat resistance of not only the terminal resin film as described in Patent Document 2, but also the exterior material. On the other hand, if a thermoplastic resin with a high melting point as described in Patent Document 2 (for example, the melting point of PET is 260° C. and the melting point of PPS is 280° C.) is to be used as a heat-sealing resin for an exterior material as described in Patent Document 1, the temperature during heat sealing must be high, and the base layer resin is required to have higher heat resistance than the heat-sealing resin, which places great limitations on practical use.

[0011] In addition, as described in Patent Document 3, low water vapor permeability is required for the heat-sealing resin used in the exterior material. However, according to the findings of the present inventors, PET has a high water vapor permeability (water vapor permeability: 40° C., 90% RH, 1034 g / m 2 1·day·atm, and the water vapor permeability and oxygen permeability described in this specification are values ​​when the thickness is 20 μm.) When the all-solid-state secondary battery is in use, water vapor may enter the inside of the battery from the end of the heat-sealed part. PPS has a lower water vapor permeability than PET (water vapor permeability: 40°C, 90% RH, 228 to 684 g / m 2 However, this still does not provide sufficient water vapor transmission, and furthermore, PPS may become brittle when melted and cooled to harden.

[0012] In addition, when oxygen penetrates into the battery, the active material, alkali metal or alkali metal ion, is oxidized, inhibiting the deactivation of the active material, and therefore, the heat-sealing resin used in the exterior material is also required to have low oxygen permeability. However, according to the findings of the present inventors, PPS, polytetrafluoroethylene (PTFE), ethylene-polytetrafluoroethylene copolymer (ETFE), etc. have high oxygen permeability and cannot suppress the penetration of oxygen into the battery.

[0013] In view of the above circumstances, an object of the present invention is to provide an exterior material for an all-solid-state secondary battery using a heat-sealing resin, in which the heat-sealed parts between the heat-sealing resins have high adhesive strength even at high temperatures, and the heat-sealing resin has high gas barrier properties (low water vapor permeability and low oxygen permeability), and to provide an all-solid-state secondary battery having the exterior material. [Means for solving the problem]

[0014] One aspect of the present invention for solving the above problems relates to an exterior material for an all-solid-state secondary battery as set forth in the following [1] to [4]. [1] Base material layer, a barrier layer made of a metal or a compound containing a metal; and A thermal adhesive layer containing polyvinylidene fluoride having a thickness of 10 μm or more and 500 μm or less; The exterior material for an all-solid-state secondary battery is layered in this order. [2] The exterior packaging material for an all-solid-state secondary battery according to [1], wherein the polyvinylidene fluoride has a melting point of 145° C. or higher and 190° C. or lower. [3] The all-solid-state secondary battery packaging material according to [1] or [2], wherein after the heat-sealing layers of the two all-solid-state secondary battery packaging materials are heat-sealed to each other, a T-shaped peel strength between the heat-sealing layers at 130°C is 18 N / cm or more. [4] The exterior packaging material for an all-solid-state secondary battery according to any one of [1] to [3], wherein the barrier layer and the heat-sealing layer are bonded to each other with a silane coupling agent having an amino group.

[0015] Another aspect of the present invention for solving the above problems relates to an all-solid-state secondary battery as described below in [5]. [5] A positive electrode; A negative electrode; a battery element including a solid electrolyte layer disposed between the positive electrode and the negative electrode; The exterior material for an all-solid-state secondary battery according to any one of [1] to [4], which houses the battery element; An all-solid-state secondary battery having the above structure. Effect of the Invention

[0016] According to the present invention, there are provided an exterior material for an all-solid-state secondary battery using a heat-sealing resin, in which the heat-sealed parts between the heat-sealing resins have high adhesive strength even at high temperatures, and the heat-sealing resin has high gas barrier properties (low water vapor permeability and low oxygen permeability), and an all-solid-state secondary battery having the exterior material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] [Exterior material] One embodiment of the present invention relates to an exterior material for an all-solid-state secondary battery, the exterior material including a base layer, a barrier layer which is a metal foil, and a thermal fusion layer which includes polyvinylidene fluoride and has a thickness of 10 μm to 500 μm. Hereinafter, the all-solid-state secondary battery is also simply referred to as a "battery."

[0018] (base material layer) The substrate layer is a layer that imparts strength to the exterior material, heat resistance (shape retention) during heat fusion to the exterior material, scratch resistance (particularly protection of the barrier layer), chemical resistance, insulation, fixation of the relative positions of the components of the battery element, and good adhesion between the electrodes and the solid electrolyte layer to the battery. The substrate layer is preferably a resin layer. In this specification, the term "resin layer" means a layer in which the majority of the material constituting the layer is resin, for example, a layer in which 50% by mass or more and 100% by mass or less, preferably 70% by mass or more and 100% by mass or less, is resin, based on the total mass of the layer. The substrate layer may be a single layer, or may be a laminate of multiple layers with different resin types.

[0019] The material of the base material layer is not particularly limited, and may be polyester resin, polyamide resin, polyolefin resin, acrylic resin, fluororesin, polyurethane resin, polyphenylene sulfide resin, polyether ether ketone resin, epoxy resin, phenol resin, etc. Among these, from the viewpoint of improving the moldability of the exterior material, polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate are preferred, and from the viewpoint of improving the elasticity of the exterior material, polyamide resins such as nylon 6, nylon 66, nylon 9T, nylon 10, nylon 11, and nylon 12 are preferred.

[0020] In addition to these resins, the base layer may contain additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents.

[0021] The thickness of the substrate layer is not particularly limited as long as it can function as a substrate, but is preferably 1 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, even more preferably 10 μm or more and 40 μm or less, and particularly preferably 20 μm or more and 35 μm or less. The thicker the substrate layer, the more fully the above-mentioned function of the substrate layer can be exhibited. On the other hand, from the viewpoint of reducing the thickness of the exterior material and increasing the relative capacity of the battery element that can be accommodated in the battery, it is preferable that the thickness of the substrate layer is not too thick. From the viewpoint of balancing these, it is preferable that the thickness of the substrate layer is adjusted within the above range.

[0022] (Barrier layer) The barrier layer is a layer for preventing the intrusion of water into the inside of the battery. A plurality of barrier layers may be provided.

[0023] The material of the barrier layer is not particularly limited as long as it has sufficiently low moisture permeability and higher heat resistance than the heat-sealing layer resin, and is preferably a metal or a compound containing a metal such as a metal oxide or metal sulfide. Specifically, a plate, foil, or vapor-deposited film made of a pure metal such as aluminum, steel, nickel, titanium, or copper, an alloy such as an aluminum alloy, stainless steel, or titanium alloy, or a metal compound such as a metal oxide or metal sulfide is preferable. Among these, a foil or vapor-deposited film made of a pure metal or alloy is more preferable, and an aluminum foil, an aluminum alloy foil, or a stainless steel foil is even more preferable.

[0024] The barrier layer may have a film on its surface formed by hydrothermal modification treatment, chemical conversion treatment, anodizing treatment, sterilization treatment, coating treatment, etc. The film may be, for example, a corrosion-resistant film formed on the heat-sealing layer side (the battery element side when the battery is formed).

[0025] The thickness of the barrier layer is preferably 1 μm or more and 200 μm or less, more preferably 1 μm or more and 100 μm or less, even more preferably 5 μm or more and 80 μm or less, and even more preferably 10 μm or more and 70 μm or less. The thicker the barrier layer is, the more fully the above-mentioned function of the barrier layer can be exhibited. On the other hand, from the viewpoint of reducing the thickness of the exterior material to increase the relative capacity of the battery element that can be accommodated in the battery and to improve the processability of the exterior material, it is preferable that the thickness of the barrier layer is not too thick. From the viewpoint of balancing these factors, it is preferable that the thickness of the barrier layer is adjusted within the above range.

[0026] (Heat-sealing layer) The heat-sealing layer is a layer for forming a sealed package containing the battery element by heat-sealing with a heat-sealing layer of an exterior material that is mated with the battery element at the periphery of the battery element. In this embodiment, the heat-sealing layer is a layer made of a resin containing polyvinylidene fluoride.

[0027] According to the findings of the present inventors, polyvinylidene fluoride has a relatively high melting point and is therefore unlikely to soften or melt even at high temperatures, and therefore a thermally adhesive layer containing polyvinylidene fluoride can improve the heat resistance of the exterior material and improve the input / output characteristics when the battery is operated at high temperatures.

[0028] In addition, polyvinylidene fluoride can increase the heat seal strength after the heat seal layers are heat-sealed together. In particular, polyvinylidene fluoride can sufficiently increase the heat seal strength at a high temperature of about 130°C, compared to other resins with high melting points. Therefore, polyvinylidene fluoride can suppress the deterioration of the sealing property of the battery caused by the peeling of the heat seal layer when the battery is used at a relatively high temperature.

[0029] Furthermore, polyvinylidene fluoride has the characteristic of low oxygen permeability and water vapor permeability. Therefore, polyvinylidene fluoride inhibits the movement of oxygen and water vapor through the heat-sealing layer, and can suppress the deterioration of the battery element and the generation of hydrogen sulfide caused by oxygen and water vapor entering the inside of the battery. In contrast, for example, polytetrafluoroethylene (PTFE) and ethylene-polytetrafluoroethylene copolymer (ETFE) have low water vapor permeability but high oxygen permeability, PET has high water vapor permeability, and PPS has high oxygen and water vapor permeability. Polyvinylidene fluoride is a thermoplastic resin with a relatively high melting point that can be used for the heat-sealing layer of the exterior material because it has both of these properties. In addition, since the heat-sealing layer is in direct contact with the positive and negative electrodes, it is exposed to the oxidation and reduction potential from these electrodes. In contrast, polyvinylidene fluoride is difficult to oxidize and reduce, so it can increase the stability of the heat-sealing layer. Due to the above-mentioned effects, polyvinylidene fluoride can increase the durability of a battery using an exterior material containing polyvinylidene fluoride.

[0030] Polyvinylidene fluoride may be a homopolymer containing only constituent units derived from vinylidene fluoride, or may be a copolymer containing constituent units derived from vinylidene fluoride and constituent units derived from a monomer other than vinylidene fluoride. When it is a copolymer, polyvinylidene fluoride may be a random copolymer or a block copolymer.

[0031] Examples of the monomer other than the vinylidene fluoride include fluorine-containing alkyl vinyl compounds, unsaturated dibasic acids or unsaturated dibasic acid monoesters, and compounds containing a vinyl group and a polar group (hereinafter also referred to as "polar group-containing compounds").

[0032] The fluorine-containing alkylvinyl compound is a compound having one or more vinyl groups and an alkyl group, in which one or more hydrogen atoms of the alkyl group are substituted with fluorine or the vinyl group is bonded to fluorine, provided that the fluorine-containing alkylvinyl compound does not include vinylidene fluoride.

[0033] Specific examples of the fluorine-containing alkyl vinyl compound include compounds having one vinyl group, such as vinyl fluoride, trifluoroethylene, tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, hexafluoroethylene, fluoroalkyl vinyl ether, and perfluoromethyl vinyl ether, as well as crosslinkable compounds having multiple vinyl groups, such as perfluorodivinyl ether and perfluoroalkylene divinyl ether.

[0034] The unsaturated dibasic acid is an unsaturated dicarboxylic acid or a derivative thereof. Examples of the unsaturated dibasic acid include compounds in which two carboxyl groups are bonded with a linear or branched unsaturated alkylene group having 1 to 6 carbon atoms, and specific examples thereof include maleic acid, fumaric acid, itaconic acid, and citraconic acid.

[0035] The unsaturated dibasic acid monoester is an ester compound derived from the unsaturated dibasic acid, and specific examples thereof include maleic acid monomethyl ester, maleic acid monoethyl ester, citraconic acid monomethyl ester, and citraconic acid monoethyl ester.

[0036] Examples of the polar group-containing compound include (meth)acrylic acid, 2-carboxyethyl (meth)acrylate, (meth)acryloyloxyethyl succinate, (meth)acryloyloxypropyl succinate, and glycidyl (meth)acrylate.

[0037] The melting point of polyvinylidene fluoride varies depending on whether it is a homopolymer or a copolymer, and, if it is a copolymer, on the type (structure) and amount of the constituent units derived from the monomers other than vinylidene fluoride. From the viewpoint of further improving the heat resistance of the exterior material and from the viewpoint of more sufficiently improving the bondability at a relatively high temperature of about 130°C, the melting point of polyvinylidene fluoride is preferably 145°C or higher and 190°C or lower, more preferably 155°C or higher and 190°C or lower, even more preferably 165°C or higher and 180°C or lower, and particularly preferably 170°C or higher and 180°C or lower.

[0038] The melting point of the vinylidene fluoride polymer is a value measured by calorimetry using a differential scanning calorimeter (DSC). Specifically, 10 mg of the vinylidene fluoride polymer is weighed into an aluminum pan, which is placed in a DSC. After replacing the inside of the DSC with pure nitrogen gas, pure nitrogen gas is passed at a flow rate of 100 ml / min, and the temperature is raised from room temperature to 230°C at 10°C / min (first heating), and after holding at 230°C for 10 minutes, the temperature is lowered from 230°C to 30°C at 10°C / min (first cooling), and further raised from 30°C to 230°C at 10°C / min (second heating), and the melting peak is identified by DSC. The maximum melting peak temperature observed in the second heating is taken as the melting point of the vinylidene fluoride polymer.

[0039] In addition, from the viewpoint of further improving the heat resistance of the exterior material, further improving the bonding property at a relatively high temperature of about 130°C, further reducing the oxygen permeability and water vapor permeability of the exterior material, and further fully exerting the above-mentioned effects specific to polyvinylidene fluoride, polyvinylidene fluoride is preferably a homopolymer of vinylidene fluoride. Even when it is a copolymer, it is preferable that the ratio of vinylidene fluoride is higher, and for example, the ratio of the constituent units derived from vinylidene fluoride to the total mass of the constituent units contained in the polyvinylidene fluoride copolymer is preferably 80% by mass or more and less than 100% by mass, more preferably 90% by mass or more and less than 100% by mass, even more preferably 95% by mass or more and less than 100% by mass, and particularly preferably 98% by mass or more and less than 100% by mass.

[0040] In order to fully exert the above-mentioned effects of polyvinylidene fluoride, the content of polyvinylidene fluoride in the total mass of the heat-sealing layer is preferably 70% by mass or more and 100% by mass or less, and more preferably 95% by mass or more and 100% by mass or less.

[0041] The heat-sealing layer may contain resins other than polyvinylidene fluoride, elastomers for imparting impact resistance, lubricants, antioxidants, slip agents, flame retardants, antiblocking agents, light stabilizers, dehydrating agents, tackifiers, and crystal nucleating agents, etc. However, from the viewpoint of fully exhibiting the above-mentioned properties due to polyvinylidene fluoride, the total amount of these components other than polyvinylidene fluoride contained in the total mass of the heat-sealing layer is preferably 0% by mass or more and 30% by mass or less, more preferably 0% by mass or more and 5% by mass or less.

[0042] The thickness of the heat-sealing layer is 10 μm or more and 500 μm or less. When the thickness of the heat-sealing layer is 10 μm or more, the heat resistance of the packaging material can be further improved, and the bonding strength at a relatively high temperature of about 130° C. can be more sufficiently increased. Although the upper limit of the thickness of the heat-sealing layer is not particularly specified, it is set to 500 μm or less from the viewpoint of making heat fusion easier. From the above viewpoint, the thickness of the heat-sealing layer is preferably 20 μm or more and 300 μm or less, more preferably 30 μm or more and 250 μm or less, and even more preferably 80 μm or more and 230 μm or less.

[0043] (Exterior material composition, etc.) The exterior material is formed by laminating the above-mentioned base material layer, barrier layer, and heat-sealing layer in this order. When the exterior material is made into a package for housing a battery, the exterior material is arranged so that the base material layer faces away from the battery element (outside) and the heat-sealing layer faces the battery element (inside).

[0044] The exterior material may have layers other than the layers described above. For example, the exterior material may have a protective layer of the exterior agent that is disposed on the outer side of the base material layer when the exterior material is made into a package.

[0045] The exterior material may also have an adhesive for bonding the layers included in the exterior material.

[0046] The adhesive may be a resin adhesive such as a polyolefin-based, polyurethane-based, or epoxy-based adhesive, or may be a coupling agent such as a silane coupling agent or a titanium coupling agent. Among these, from the viewpoint of further increasing the bonding strength at a relatively high temperature of about 130°C, a coupling agent is preferred, a silane coupling agent is more preferred, and a silane coupling agent having an amino group is even more preferred. A silane coupling agent having an amino group can strongly bond the barrier layer and the PVDF heat-sealing layer by chemically bonding the amino group with PVDF. In addition, since the adhesive layer does not harden or decompose due to heating at 130°C, or there is no excessive reaction with PVDF, it is considered that the bonding strength is increased in the above-mentioned high temperature range.

[0047] When the exterior material is used to make a package that houses a battery, the battery element is covered with two sheets of upper and lower exterior material so that the base layer is on the opposite side (outside) from the battery element and the heat-sealing layer is on the battery element side (inside). In this case, the exterior material is caused to protrude outward from the periphery of the battery element, and the heat-sealing layers of the upper and lower two exterior materials in the protruding portion are heat-sealed together by heating and pressurizing. This makes it possible to form a sealed package that houses the battery element inside. Note that the temperature for the heat-sealing may be set in the range of not less than the melting point of polyvinylidene fluoride contained in the heat-sealing layer and not more than the melting point + 10°C.

[0048] The exterior material uses a heat-sealing layer containing polyvinylidene fluoride, so that the heat seal strength between the heat-sealing layers by heat fusion is high even at high temperatures. Specifically, two exterior materials cut into strips of 100 mm long x 15 mm wide are stacked so that the heat-sealing layers face each other, and while pressurized to 0.5 MPa, they are heated for 3 seconds at a temperature equal to or higher than the melting point of polyvinylidene fluoride contained in the heat-sealing layer and equal to or lower than the melting point + 10°C, and then left to stand at room temperature for 24 hours or more, and slowly cooled to room temperature to heat-seal the heat-sealing layers. At this time, 25 mm from one end of the longitudinal direction of the two stacked exterior materials is not heat-sealed, and the remaining 75 mm area is heat-sealed. Then, the heat-fused body cut to a width of 10 mm is used as a T-shaped test piece, and the non-heat-fused end of the T-shaped test piece is opened in the opposite direction until it is perpendicular to the heat-fused part and the non-fused part becomes straight, and the heat-fused part is peeled off by moving the non-heat-fused ends in the straight line direction and in the opposite direction at a speed of 50 mm / min under the condition of 130° C. At this time, the T-shaped peel strength (N / cm), obtained by dividing the maximum stress (N) at a peel distance of 5 mm to 50 mm by the width (cm) of the heat-fused body, is preferably 18 N / cm or more, more preferably 25 N / cm or more, and even more preferably 38 N / cm or more.

[0049] [All-solid-state secondary battery] The above-mentioned exterior material can be used as an exterior material for an all-solid-state secondary battery. The all-solid-state secondary battery including the above-mentioned exterior material has a battery element including a positive electrode, a negative electrode, a solid electrolyte layer disposed between the electrodes, and a terminal for extracting current from each electrode, and has an exterior material that houses the battery element except for a part of the current extracting terminal. At this time, the exterior material is a sealed package that houses the battery element in the exterior material by heat-sealing layers to each other around the periphery of the battery element. Here, the current extracting terminal is partially heat-sealed together with the exterior material and is exposed to the outside of the sealed package.

[0050] The type, material, shape, size, etc. of the battery element are not particularly limited.

[0051] For example, the positive electrode may be any positive electrode active material layer for an all-solid-state secondary battery, in which a positive electrode active material layer is formed on a current collector, contains a positive electrode active material, and optionally contains a solid electrolyte, a conductive assistant, a binder, and the like.

[0052] Examples of materials constituting the positive electrode current collector include stainless steel (SUS), aluminum, nickel, iron, titanium, and alloys thereof.

[0053] The thickness of the positive electrode current collector is appropriately set depending on the size of the all-solid-state battery, and is preferably about 10 to 1000 μm.

[0054] Examples of the positive electrode active material include LiCoO2, LiNiO2, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, and Li(Ni 1 / 2 Mn 1 / 2 )O2, LiMn2O4, and Li(Ni 1 / 2 Mn 3 / 2 )O4, and olivine structure type positive electrode active materials such as LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. Sulfides such as TiS2, MoS2, FeS, FeS2, CuS, and Ni3S2), and NbSe3, etc. may also be used.

[0055] The positive electrode active material layer preferably further contains a solid electrolyte. This can improve the ionic conductivity in the positive electrode active material layer. The solid electrolyte contained in the positive electrode active material layer is the same as the solid electrolyte exemplified below.

[0056] Examples of the conductive assistant include metals, graphite such as natural graphite and artificial graphite, carbon fiber, vapor grown carbon fiber (VGCF), carbon black such as acetylene black and ketjen black, needle coke, nanocarbon such as carbon nanotubes (CNT), and the like.

[0057] Examples of the binder include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, and cellulose; thermoplastic elastomers such as styrene-butadiene-styrene block copolymer (SBS), ethylene-propylene-diene terpolymer (EPDM), styrene-ethylene-butadiene-ethylene copolymer (SEBS), and styrene-isoprene-styrene block copolymer (SIS); and fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and ethylene-polytetrafluoroethylene copolymer (ETFE).

[0058] In addition, the negative electrode may be any negative electrode active material layer for an all-solid-state secondary battery, in which a negative electrode active material layer is formed on a current collector, and the negative electrode active material layer contains a negative electrode active material, and optionally contains a solid electrolyte, a conductive assistant, a binder, and the like.

[0059] Examples of materials that can be used to form the negative electrode current collector include stainless steel (SUS), copper, and nickel.

[0060] The thickness of the negative electrode current collector is appropriately set depending on the size of the all-solid-state battery, and is preferably about 10 to 1000 μm.

[0061] Examples of the negative electrode active material include metal lithium, metals such as Sn, Si, Al, Ge, Sb, P, and In, Nb2O5, Li4Ti5O 12 metal oxides such as SiO, composites of metals and metal oxides such as SiO, graphitic materials such as artificial graphite and natural graphite, and amorphous carbons such as graphitizable carbon and non-graphitizable carbon.

[0062] The negative electrode active material layer preferably further contains a solid electrolyte. This can improve the ionic conductivity in the negative electrode active material layer. The solid electrolyte contained in the negative electrode active material layer is the same as the solid electrolyte exemplified below as the solid electrolyte.

[0063] Examples of the conductive assistant and binder that can be contained in the negative electrode active material layer include the same substances as the conductive assistant and binder that can be contained in the positive electrode active material layer.

[0064] Examples of the solid electrolyte include sulfide-based solid electrolytes such as Li2S-P2S5, Li2S-SiS2, LiX-Li2S-SiS2, LiX-Li2S-P2S5, LiX-Li2O-Li2S-P2S5, LiX-Li2S-P2O5, LiX-Li3PO4-P2S5, and Li3PS4 (for example, "Li2S-P2S5" in the above examples represents a material obtained using a raw material composition containing Li2S and P2S5. In addition, "X" in each of the above materials represents a halogen atom.), and Li 6.25 La3Zr2Al 0.25 O 12 , Li3PO4, Li 3+x PO 4-x N x The oxide-based solid electrolytes include those mentioned above. EXAMPLES

[0065] Hereinafter, the embodiments of the present invention will be described in detail based on examples and comparative examples, but the present invention is not limited to these.

[0066] 1. Measurement of physical properties of heat-sealed layer In each of the following Examples and Comparative Examples, the melting point, oxygen permeability, and water vapor permeability of the heat-sealing layer were measured by the following methods.

[0067] (1m 2 permeability rate) The oxygen permeability test was performed in accordance with JIS K7126-2:2006 using an isobaric oxygen permeability tester (MOCON OX-TRAN 2 / 22) under the conditions of a temperature of 30°C, a relative humidity of 80%, a measurement time of 24 hours, and 1 atmospheric pressure. 2 Oxygen permeability per surface area (cc / m 2 This was calculated as the oxygen permeability of a film with a thickness of 20 μm using the following formula:

[0068]

number

[0069] (1m 2 Water vapor transmission rate per unit The water vapor transmission rate of each resin film used in the fusion layer was measured using a water vapor transmission rate measuring device (MOCON PERMATRAN-W 3 / 33) using the isobaric method under the conditions of a temperature of 40°C, a relative humidity of 90%, a measurement time of 24 hours, and 1 atmosphere, in accordance with JIS K7129-2:2019. 2 Water vapor transmission rate per unit area (g / m 2 / d / atm) was measured by the following method. This was calculated as the water vapor transmission rate of a film with a thickness of 20 μm using the following formula.

[0070]

number

[0071] (Resin melting temperature (melting point)) The melting temperature (melting point) of each resin can be measured by a differential scanning calorimeter. Specifically, a DSC 3+ manufactured by METTLER TOLEDO was used as the analyzer. 10 mg of vinylidene fluoride polymer was weighed on an aluminum pan, which was placed in the analyzer, and the inside of the analyzer was replaced with pure nitrogen gas, and then pure nitrogen gas was passed through at a flow rate of 100 ml / min. The temperature was raised from room temperature to 230°C at 10°C / min (first heating), and the temperature was held at 230°C for 10 minutes, after which the temperature was lowered from 230°C to 30°C at 10°C / min (first cooling), and the temperature was further raised from 30°C to 230°C at 10°C / min (second heating) to measure the melting peak. The temperature of the melting peak having the maximum area observed in the second heating was taken as the melting point of the vinylidene fluoride polymer.

[0072] The melting points of resins other than polyvinylidene fluoride, such as PP, PTFE, and ETFE, were also measured using a differential scanning calorimeter (METTLER TOLEDO DSC 3+). Specifically, 10 mg of these resins were weighed into an aluminum pan, which was placed in the analyzer, and the inside of the analyzer was replaced with pure nitrogen gas. Then, pure nitrogen gas was passed through the pan at a flow rate of 100 ml / min, and the temperature was raised from room temperature at a rate of 10°C / min to measure the melting peak. The temperature of the melting peak having the maximum area observed during the temperature rise was taken as the melting point.

[0073] 2. Preparation and evaluation of exterior materials Example 1 A 50 μm thick aluminum (Al) foil (A1N30H-H18, manufactured by UACJ Foil Co., Ltd.) was immersed in a 5 wt% aqueous solution of an alkaline immersion degreaser (SK-144, manufactured by JCU Co., Ltd.) at 70 ° C for 1 minute. After washing with ion-exchanged water and drying, a 1 wt% aqueous solution of an amino group-containing silane coupling agent (hereinafter also simply referred to as "coupling agent") was applied to one side and dried. Next, a 50 μm thick polyvinylidene fluoride (PVDF) film (Kureha Co., Ltd., homopolymer type #1000) was placed on the coupling agent-coated side of the aluminum foil, and pressed at 200 ° C, 2 MPa, and 5 minutes using a heater plate molding machine (P4054-00, manufactured by NPA System Co., Ltd.) to obtain a laminated film of a PVDF film and an aluminum foil. A two-liquid curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to the aluminum foil on the side of the laminated film that was not laminated with PVDF, and a polyethylene terephthalate (PET) film (50 μm) was laminated thereon. The resulting laminate was aged and heated to obtain an exterior body for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PVDF film). The exterior body was thermally fused at 180° C., and the T-peel strength was measured.

[0074] Example 2 A two-component curing urethane adhesive (polyol compound and aromatic isocyanate compound) was applied to the Al foil immersed in the alkaline immersion degreaser and washed with ion-exchanged water in Example 1, and a 50 μm thick PVDF film (Kureha Corporation, #1000) was laminated thereon. A PET film (50 μm) was adhered to the Al foil on the side of the laminated film where the PVDF was not laminated in the same manner as in Example 1, to obtain an exterior body for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PVDF film). The exterior body was heat-sealed at 180° C., and the peel strength was measured.

[0075] Example 3 Except for changing the thickness of the PVDF to 100 μm and using a 100 μm thick stainless steel foil (Hikari Corporation, HS0132) instead of the 50 μm thick Al foil, an outer casing for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (stainless steel foil) / thermal adhesive layer (PVDF) was obtained in the same manner as in Example 1. The outer casing was thermally fused at 180° C., and the peel strength was measured.

[0076] Example 4 Except for changing the thickness of the PVDF film to 30 μm, an outer casing for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PVDF film) was obtained in the same manner as in Example 1. The outer casing was thermally fused at 180° C., and the peel strength was measured.

[0077] Example 5 Except for changing the thickness of the PVDF film to 200 μm, an outer casing for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PVDF film) was obtained in the same manner as in Example 1. The outer casing was thermally fused at 180° C., and the peel strength was measured.

[0078] Example 6 Except for changing the thickness of the PVDF film to 100 μm, an outer casing for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PVDF film) was obtained in the same manner as in Example 1. The outer casing was thermally fused at 180° C., and the peel strength was measured.

[0079] Example 7 Except for using a homopolymer high polymerization type PVDF film (Kureha Corporation, homopolymer #1300), an outer casing for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PVDF film) was obtained in the same manner as in Example 6. The outer casing was thermally fused at 180° C., and the peel strength was measured.

[0080] Example 8 Except for using a copolymer type PVDF film (Kureha Corporation, Copolymer #2300), an outer casing for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PVDF film) was obtained in the same manner as in Example 6. The outer casing was thermally fused at 180° C., and the peel strength was measured.

[0081] Example 9 An Al foil coated with a coupling agent on one side was prepared in the same manner as in Example 1. Next, a PET film having a thickness of 90 μm was laminated on the coupling agent-coated surface of the aluminum foil, and the laminate was pressed at 260 ° C., 2 MPa, and 5 minutes using the heater plate molding machine to obtain a laminated film of a PET film and an aluminum foil. The same coupling agent as in Example 1 was applied to the aluminum foil on the side of the laminated film on which the PET film was not laminated, and a PVDF film having a thickness of 50 μm (Kureha Corporation, homopolymer type #1000) was laminated, and the laminate was pressed at 180 ° C., 2 MPa, and 5 minutes using the heater plate molding machine to obtain an outer casing for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / a barrier layer (Al foil) / a heat-sealing layer (PVDF film). The outer casing was heat-sealed at 160 ° C., and the peel strength was measured.

[0082] Comparative Example 1 Except for changing the thickness of the PVDF film to 5 μm, an outer casing for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PVDF film) was obtained in the same manner as in Example 1. The outer casing was thermally fused at 180° C., and the peel strength was measured.

[0083] Comparative Example 2 A commercially available aluminum laminate film for small consumer batteries (purchased from Hosen Co., Ltd., substrate: nylon with a thickness of 25 μm, barrier layer: aluminum foil with a thickness of 40 μm, heat-sealing layer: polypropylene resin, pouch film, packaging material) was used. The aluminum laminate film was heat-sealed at 140°C, and the peel strength was measured.

[0084] Comparative Example 3 An attempt was made to produce an exterior body for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (PTFE film) in the same manner as in Example 1, except that a 60 μm thick polytetrafluoroethylene (PTFE) film (Yodogawa Hutech Co., Ltd., Yodoflon PTFE film) was used as the thermal adhesive layer instead of the PVDF film, but the PTFE film did not bond to the barrier layer. In addition, an attempt was made to thermally bond PTFE films together, but thermal fusion was not possible at a thermal fusion temperature of 180°C.

[0085] Comparative Example 4 An exterior body for an all-solid-state secondary battery consisting of a laminate of a base layer (PET film) / barrier layer (Al foil) / thermal adhesive layer (ETFE film) was obtained in the same manner as in Example 1, except that a 50 μm-thick ethylene-polytetrafluoroethylene (ETFE) film (manufactured by Toray Advanced Film Co., Ltd., ETFE film) was used as the thermal adhesive layer instead of the PVDF film and the pressing temperature was set to 260° C. The exterior body could not be thermally sealed at 180° C.

[0086] Comparative Example 5 The exterior body described in Comparative Example 4 was heat-sealed at 260° C., and the peel strength was measured.

[0087] 3. Evaluation For the exterior materials produced in each Example and Comparative Example, the T-shaped peel strength was measured by the following method. Unless otherwise specified, the T-shaped peel strength was measured under the following conditions for exterior materials in which the heat-sealing layers were heat-sealed to each other at a temperature between the melting point of the heat-sealing layer and the melting point + 10°C (specific temperatures are described in the explanation of each Example and Comparative Example). The entire exterior material (base material layer / barrier layer / heat-sealing layer) was fixed with the gripping tools of a universal testing machine and the T-shaped peel test was performed, and it was confirmed that peeling occurred at the part where the heat-sealing layers were heat-sealed to each other in the peel test.

[0088] The laminate was cut into several strips of 100 mm long x 15 mm wide, and two cut-out laminates were stacked with the heat-sealing layer facing each other, placed in a heat seal tester (TP-701-C, manufactured by Tester Sangyo Co., Ltd.), and heated for 3 seconds under a pressure (load) of 0.5 MPa so that the heat-sealing layer reached a specified temperature for 3 seconds to produce a heat-sealed body. At this time, 25 mm from one end in the longitudinal direction was not heat-sealed, and the remaining 75 mm area was heat-sealed. After heat-sealing, the heat-sealed body was left to stand at room temperature and slowly cooled, and after 24 hours or more, the heat-sealed body was cut into a width of 10 mm to prepare a T-shaped peel test piece.

[0089] A T-shaped peel test was performed using a universal testing machine (A&D Co., Ltd., RTC-1210A) placed in a thermostatic chamber maintained at 130°C. The non-thermally fused ends of the T-shaped peel test specimen were opened in opposite directions until they were perpendicular to the heat-fused portion, and each was held by the grip of the testing machine. At this time, the non-fused portion was made to be in a straight line between the grips. After confirming that the temperature inside the thermostatic chamber was 130°C, the grip of the universal testing machine was moved in the tensile direction at a speed of 50 mm / min, and the applied stress relative to the peel distance of the grip was recorded. The maximum stress (N) at a peel distance of 5 mm to 50 mm was divided by the width (cm) of the heat-fused body to obtain the peel strength (N / cm).

[0090] 4.Results Table 1 shows various physical properties, heat fusion temperatures, and T-peel strengths of the materials used to prepare the heat seal layers and barrier layers in each of the Examples and Comparative Examples.

[0091] [Table 1]

[0092] As is clear from Table 1, when a heat-sealing layer containing polyvinylidene fluoride and having a thickness of 10 μm or more and 500 μm or less is used as an exterior material, the heat-sealing temperature does not need to be very high, and the adhesive strength after heat-sealing at around 130°C is high.

[0093] This application claims priority to Japanese Application No. 2022-022017, filed on February 16, 2022, and the contents of the specification and claims of that application are incorporated by reference into this application. [Industrial Applicability]

[0094] The exterior material of the present invention does not require a very high heat fusion temperature, and has high adhesive strength after heat fusion at about 130° C. The exterior material is very useful as an exterior material for all-solid-state secondary batteries, particularly all-solid-state secondary batteries that are expected to be used at high temperatures.

Claims

1. base material layer, a barrier layer made of a metal or a compound containing a metal; and A thermal adhesive layer containing polyvinylidene fluoride having a thickness of 10 μm or more and 500 μm or less; The exterior material for an all-solid-state secondary battery is layered in this order.

2. The packaging material for an all-solid-state secondary battery according to claim 1 , wherein the polyvinylidene fluoride has a melting point of 145° C. or higher and 190° C. or lower.

3. 3. The all-solid-state secondary battery packaging material according to claim 1, wherein the heat-sealing layers of the two all-solid-state secondary battery packaging materials have a T-shaped peel strength of 18 N / cm or more at 130°C after the heat-sealing layers of the two all-solid-state secondary battery packaging materials are heat-sealed to each other.

4. 3. The packaging material for an all-solid-state secondary battery according to claim 1, wherein the barrier layer and the heat-sealing layer are bonded to each other by a silane coupling agent having an amino group.

5. A positive electrode; A negative electrode; a battery element including a solid electrolyte layer disposed between the positive electrode and the negative electrode; The all-solid-state secondary battery exterior material according to claim 1 or 2, which houses the battery element; An all-solid-state secondary battery having the above structure.

Citation Information

Patent Citations

  • Exterior material for power storage device and power storage device

    JP2020030975A

  • Exterior material for power storage device and power storage device using the same

    JP2022015907A

  • Layered body, bag, and lithium ion cell

    WO2016148071A1

  • Resin film for terminal, and power storage device using resin film for terminal

    WO2020004412A1

  • Exterior material for all-solid-state battery, method for manufacturing same, and all-solid-state battery

    WO2020153458A1